Histological changes of immediate skin expansion of the distal limb of rats - Ali, Ahmed Khalaf; Abubakar, Adamu Abdul; Kaka, Ubedullah; Radzi, Zamri; Khairuddin, Nurul Hayah; Yusoff, Md Sabri Mohd; Loqman, Mohamad Yusof (Veterinary World, 2018)
Aim: Tissue expansion is an applicable technique to reconstruct many surgical defects. The aim of this research was to evaluate the histological changes caused by immediate skin tissue expansion in rats as an animal model. Materials and Methods: Immediate skin tissue expansion in 18 adult female rats was performed using three different sizes (small, medium, and big) of polymethylmethacrylate tissue expanders at the dorsal surface of the metatarsal area of the right limb. The contralateral limb was served as the control. The tissue expanders were surgically implanted and kept for 15 days. Results: The immediate skin expansion resulted in histological changes such as the increased thickness of the epidermal layer, the reduction of the dermal layer, an elevated number of fibroblast as well as increased vascularity. Furthermore, skin adnexal structures such as hair follicles and sebaceous glands were farther apart. Conclusion: The rat skin was able to rapidly adjust and compensate against a specific range of immediate mechanical expansion. The histological changes suggest that the tissues were prepared to withstand the increased external forces, in addition to create possibly additional skin in a relatively short-term period.